Methodological substantiation of teaching mathematics to university students on the basis of the activity approach (Pedagogy of Higher and Secondary Education, 2011)
Different approaches to determination concept of teaching are analysed in the article. Methodological ground of mathematics teaching in a technical university on the basic of activities approach are formulated.
Keywords: the concept of; teaching mathematics at a technical university; learning on the basis of the activity approach